Studi Etnografi Komunikasi Tradisi Selapanan Pada Kehidupan Sosial Masyarakat Desa Tempur Kecamatan Keling Kabupaten Jepara Jawa Tengah - Aminaturrofiqoh; Moh. Edy Marzuki (Brand Communication, 2024)
This research aims to understand the Selapanan Bayi Tradition carried out by the people of Tempur Village, Keling District, Jepara Regency, Central Java, as well as to explore the meaning and form of communication that occurs in the implementation of the tradition. The Selapanan tradition, which is a ceremony to save a baby at the age of 35 days, is an important part of the life cycle of a society rich in cultural and spiritual values. The ethnographic approach of communication is used to describe the patterns of behavior, habits and ways of life of the people of Tempur Village in carrying out the Selapanan Tradition. Through non-participant observation, namely with in-depth interviews with the local community, this study found that the Selapanan Tradition is not only a form of respect for ancestors, but also as a means of maintaining the safety and welfare of babies and their families from the threat of evil spirits. The Selapanan Bayi tradition contains various symbols and meanings that are believed to have moral and social values. The ceremonial process involving salvation, joint prayer and cutting of the baby's hair illustrates the community's expectations for the health and safety of the baby. This study also identifies a degradation in the implementation of traditions due to modernization and social changes, but the people of Tempur Village try to preserve this tradition so that it is still known and appreciated by the younger generation.This research emphasizes the importance of understanding and preserving local traditions as part of the cultural and social identity of a community. The Selapanan Bayi tradition in Tempur Village provides a deep insight into how society interprets life, death, and life cycles through communication and rituals rich in symbolism.